Verification of serum albumin elevating effect of cell-free and concentrated ascites reinfusion therapy for ascites patients: a retrospective controlled cohort study - Yosuke Yamada (Nature Portfolio, 2019)
Abstract Cell-free and concentrated ascites reinfusion therapy (CART) is frequently used to treat refractory ascites in Japan. However, its efficacy remains unclear. This controlled cohort study verified the serum albumin elevating effect of CART by comparisons with simple paracentesis. Ascites patients receiving CART (N = 88) or paracentesis (N = 108) at our hospital were assessed for the primary outcome of change in serum albumin level within 3 days before and after treatment. A significantly larger volume of ascites was drained in the CART group. The change in serum albumin level was +0.08 ± 0.25 g/dL in the CART group and −0.10 ± 0.30 g/dL in the paracentesis group (P < 0.001). The CART – paracentesis difference was +0.26 g/dL (95%CI +0.18 to +0.33, P < 0.001) after adjusting for potential confounders by multivariate analysis. The adjusted difference increased with drainage volume. In the CART group, serum total protein, dietary intake, and urine volume were significantly increased, while hemoglobin and body weight was significantly decreased, versus paracentesis. More frequent adverse events, particularly fever, were recorded for CART, although the period until re-drainage was significantly longer. This study is the first demonstrating that CART can significantly increase serum albumin level as compared with simple paracentesis. CART represents a useful strategy to manage patients requiring ascites drainage.